Enhanced Modelling and Efficient Realisation of Cyber- Physical Systems - Jørgensen, Peter Würtz Vinther (Technical Report Electronics and Computer Engineering, 2014)
This report describes the work carried out for the first half of the PhD project titled Enhanced Modelling and Efficient Realisation of Cyber-Physical Systems (CPSs). The work contributions cover methods and tools to address the challenges of CPS development using a model-based approach. First the report introduces a technique to assist stakeholders in organising design information produced during modelling. Then a modelling language extension that supports reasoning about the energy consumption of the CPUs of a CPS is presented. Afterwards a technique that enables one to include real system components into the system simulation is described and finally the report presents a technology that enables construction of code generators for multiple target languages. In addition to covering the work contributions, this report also describes future work plans that will lead to the completion of the PhD project by April 2016.